Analisis Strategi Pemasaran Terkait Keputusan Pembelian Konsumen Pada Produk Akfix - Wilson Anthony Chandra (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
This study aims to analyze marketing strategies related to consumer purchasing decisions on Akfix products. In this research data collection method used is questionnaire to know the factors sought by customer in choosing product of Akfix. The sample is 100 respondents who purchase Akfix products. Data analysis method used is regression analysis and SWOT. Based on the result of the research, it is concluded that evaluation of marketing strategy applied to current product of akfix is product has average value 4.04. This means that respondents agree with the statement that respondents buy Akfix products because they already recognize the problems I am facing, respondents buy Akfix products after collecting various information, respondents buy Akfix products after evaluating various alternatives, and respondents feel satisfied after buying and using Akfix products. Factors influencing purchasing decisions are product, promotion price, and distribution. This is obtained because based on the results of analysis using SPSS, proved all variables have a significance value below 0.005. Product, promotion and distribution has a significance value of 0.000 while the price has naiai significance of 0.014. The most appropriate strategy to increase product sales akfix is the product. This is obtained because based on the results of analysis using SPSS, proved that the product variable has the largest beta value among other variables that is equal to 0.414.